A Preliminary Study on Accident Analysis of Portable Timber Sawmills Used in Mazamba Forest Plantation in Northern Malawi - Jameson T. T. Mzungu; Elisha S. Ngulube (International Journal of Forestry Research)
This study investigated the main causes of accidents, levels of injuries, and mitigation measures to wood processing accidents. Structured interviews were conducted on 45 respondents drawn from various portable sawmills. The Chi square test showed that there were highly significant differences on frequency distribution of causes of sawmill accidents. However, a principal component analysis revealed that accidents were mainly caused by inappropriate equipment setup or operation and harsh weather conditions. Secondly, results showed that the frequency distribution of responses on levels of accidents was highly significantly different among the respondents. Near-misses accounted for most of responses (55.6%). This is because near-misses are precursors to secondary accidents. Furthermore, the results showed highly significant differences on the frequency distribution of various mitigation measures available. Use of personal protective equipment and provision of special training were highly appraised. Forest workers need occupation safety and health and ergonomic knowledge before engaging in wood processing.